2022
DOI: 10.1038/s41375-022-01531-2
|View full text |Cite
|
Sign up to set email alerts
|

LocoMMotion: a prospective, non-interventional, multinational study of real-life current standards of care in patients with relapsed and/or refractory multiple myeloma

Abstract: Despite treatment advances, patients with multiple myeloma (MM) often progress through standard drug classes including proteasome inhibitors (PIs), immunomodulatory drugs (IMiDs), and anti-CD38 monoclonal antibodies (mAbs). LocoMMotion (ClinicalTrials.gov identifier: NCT04035226) is the first prospective study of real-life standard of care (SOC) in triple-class exposed (received at least a PI, IMiD, and anti-CD38 mAb) patients with relapsed/refractory MM (RRMM). Patients (N = 248; ECOG performance status of 0–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 10 publications
2
79
0
Order By: Relevance
“…Indirect treatment comparisons between the CARTITUDE-1 results and real-world SOC, in data sets comprising European and/or US patients (MAMMOTH study and the prospective LocoMMotion study), found that cilta-cel significantly improved outcomes versus real-world therapies in triple-class exposed patients with RRMM. 3,25 In a matching-adjusted indirect treatment comparison using data from the similarly designed CARTITUDE-1 14 and KarMMa 13 trials, cilta-cel appeared to have higher response rates and longer DOR and PFS than ide-cel. 26 After a MFU of 13.3 months, the ORR in the KarMMa trial was 73% across all dose cohorts (33% CR or better) and 81% with the highest dose evaluated (450 × 10 6 cells; 39% CR or better).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect treatment comparisons between the CARTITUDE-1 results and real-world SOC, in data sets comprising European and/or US patients (MAMMOTH study and the prospective LocoMMotion study), found that cilta-cel significantly improved outcomes versus real-world therapies in triple-class exposed patients with RRMM. 3,25 In a matching-adjusted indirect treatment comparison using data from the similarly designed CARTITUDE-1 14 and KarMMa 13 trials, cilta-cel appeared to have higher response rates and longer DOR and PFS than ide-cel. 26 After a MFU of 13.3 months, the ORR in the KarMMa trial was 73% across all dose cohorts (33% CR or better) and 81% with the highest dose evaluated (450 × 10 6 cells; 39% CR or better).…”
Section: Discussionmentioning
confidence: 99%
“…1 However, patients may eventually become resistant to these treatments. 2,3 Lower depth and durability of response have been reported with each successive line of therapy (LOT), 4 and patients who are refractory to multiple drug classes have suboptimal outcomes. The median overall survival (OS) with SOC is 11.2 months for patients who are refractory to < 3 prior LOT and 5.6 months for penta-refractory patients (refractory to anti-CD38 antibody, two PIs, and two IMiDs).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who are refractory to the standard drug classes (PIs, IMiDs, and anti-CD38 mAbs), otherwise known as triple-class refractory MM, have a poor prognosis (limited overall survival [OS] and progression-free survival [PFS] outcomes), with an estimated OS of less than 1 year [ 3 , 5 ]. Therapeutic options for both triple-class refractory [ 5 ] and refractory MM patients who were triple-class exposed [ 11 ] are limited, representing a population with a fairly clear unmet medical need [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed safety findings for CARTITUDE-1 18 and LocoMMotion 20,21 have been previously reported elsewhere. Unadjusted comparison of all AEs shows higher rates of AEs for cilta-cel vs.…”
Section: Comparison Of Safety Outcomesmentioning
confidence: 99%
“…This was also the case for grade 3/4 events (93.8% vs. 49.2%, Table 4). Mateos et al 21 reported AEs as being underreported for RWCP in LocoMMotion due to its observational nature. Six (6.2%) patients treated with cilta-cel and nineteen (7.7%) patients with RWCP experienced an adverse event with an outcome of death.…”
Section: Comparison Of Safety Outcomesmentioning
confidence: 99%